Pe Penerapan Model Problem-based learning (PBL) untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi Bagian-bagian Tumbuhan - Yasir Rizqa; Danil, M.; Aldyza, Nadia (Jurnal Riset Madrasah Ibtidaiyah, 2025)
People should be able to think critically about what they read and see, especially when it comes to AI and he rapid advancement of science and technology, particularly artificial intelligence, has raised concerns as humans are not always capable of critical thinking. To keep up with the changing times, individuals must be able to think critically. This study is a quantitative research that aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in helping students develop critical thinking skills. Students from UPTD SD Negeri 3 Simpang Mamplam participated in pre-tests and post-tests as part of the quantitative learning plan. Before and after the implementation of PBL in the plant parts material, critical thinking skill tests were used to collect data. The results showed that students’ critical thinking skills improved significantly, from an average score of 49.30% on the pre-test to 85% on the post-test. PBL learning steps, such as problem formulation, research, and review, were proven to enhance students' interest in learning. The PBL approach addresses the shortcomings of traditional teaching methods and allows students to think more freely, rationally, and critically. In conclusion, PBL is an effective method for helping students develop critical thinking skills.